Unwanted daughters : gender discrimination in modern India - Sekher T V (ed.); Neelambar Hatti (ed.) (Jaipur : Rawat Publications, 2010)
Papers presented at a workshop held at Institute for Social and Economic Change, Bangalore in 2005.
Keywords: Sex Discrimination Women; Sex Children; Sex Ratio; Sex Distribution; Gender Studies; Social Sciences